Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Number: 1
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

How do female entrepreneurs perform? Evidence from three developing regions - Bardasi, Elena; Sabarwal, Shwetlena; Terrell, Katherine (Small Business Economics, 2011)
Using the World Bank Enterprise Survey data, we analyze performance gaps between male- and female-owned companies in three regions—Eastern Europe and Central Asia (ECA), Latin America (LA), and Sub-Saharan Africa (SSA). Among our findings are significant gender gaps between male- and female-owned companies in terms of firm size, but much smaller gaps in terms of firm efficiency and growth (except in LA). Part of the reason women run smaller firms is that they tend to concentrate in sectors in which firms are smaller and less efficient (in ECA and SSA). By contrast, we find no evidence of gender discrimination in access to formal finance in any of the three regions, although in ECA women are less likely than men to seek formal finance. Finally, while female entrepreneurs receive smaller loans than their male counterparts, the returns from each dollar they receive is no lower in terms of overall sales revenue.
Number: 4
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and the Business Environment for New Firm Creation - Klapper, Leora F.; Parker, Simon C. (The World Bank Research Observer, 2011)
Abstract. The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differ
Number: 2 Publisher: Oxford Academic
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Small and Medium Enterprises (smes) Access to Finance in Selected East Asian Economies - Harvie, Charles; Oum, Sothea; Narjoko, Dionisius A (ERIA - Economic Research Institute for ASEAN and East Asia, 2010)
Findings from ERIA’s SME research project in FY 2009 confirms that access to finance is amongst the most critical factors determining the competitive readiness of regional SMEs and their ability to fully exploit and participate in the global economy and business opportunities from regional economic integration and, in particular, participation in regional production networks. Well recognized in the literature, access to funding is the lifeblood of any enterprise, enabling it to grow, and to generate more output and employment. There is considerable evidence to support the contention that SMEs, in particular, face a number of obstacles and problems in accessing finance, mainly related to their limited resources and perceived risk by lenders. This is particularly problematic and worrisome for policy makers, given that SMEs and entrepreneurship are widely recognized as being the key sources of dynamism, innovation, and flexibility in advanced industrialized, emerging market and developing economies, and are major net job creators in these economies. Without access to finance, SMEs are unable to invest, impairing their capacity to: improve productivity; raise competitiveness; promote innovation; generate employment; and contribute to economic growth and development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; ⛔ No DOI found